2019
DOI: 10.1128/mbio.00218-19
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Component Binds Fungal Surface Amyloid and Decreases Human Macrophage Phagocytosis and Secretion of Inflammatory Cytokines

Abstract: In patients with invasive fungal diseases, there is often little cellular inflammatory response. We tested the idea that binding of the human constitutive plasma protein serum amyloid P component (SAP) (also called PTX2) to Candida albicans dampens the innate immune response to this fungus. Many pathogenic fungi have cell surface amyloid-like structures important for adhesion and biofilm formation. Human SAP bound to fungi that expressed functional cell surface amyloid, but SAP had minimal binding to fungi wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Plasma proteins have multiple roles in controlling infections. A recent study demonstrated that human plasma protein serum amyloid P component (SAP) was able to bind to surface amyloid-like structures of C. albicans and resulted in poor recognition and ingestion of yeast cells by host macrophages (26). Combined with this previous finding, our study implies that this innate immune protein could play a critical role in defense against C. albicans infections either through indirect induction of degranulation and phagocytosis or directly by killing the pathogen.…”
Section: Discussionsupporting
confidence: 68%
“…Plasma proteins have multiple roles in controlling infections. A recent study demonstrated that human plasma protein serum amyloid P component (SAP) was able to bind to surface amyloid-like structures of C. albicans and resulted in poor recognition and ingestion of yeast cells by host macrophages (26). Combined with this previous finding, our study implies that this innate immune protein could play a critical role in defense against C. albicans infections either through indirect induction of degranulation and phagocytosis or directly by killing the pathogen.…”
Section: Discussionsupporting
confidence: 68%
“…Als1p is highly expressed in mouse models of infection and in artificial biofilms (14, 45). In contrast, Als5p is moderately expressed, and its expression can skew human macrophages toward the tolerant M2 state or lead to commensal-like interactions in a Caenorhabditis elegans infection model (46, 47). These independent biological roles are reflected in differences in the activities of Als1p and Als5p in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SAP binds to functional amyloid displayed in the fungal surface in several deep infections [26,27]. In invasive candidiasis, SAP binds to functional amyloid on the surface of the fungi; this inhibits macrophage phagocytosis and reduces the secretion of inflammatory cytokines [28].…”
Section: Discussionmentioning
confidence: 99%